2013
DOI: 10.1177/0954406213517675
|View full text |Cite
|
Sign up to set email alerts
|

Essential reformulations for optimization of highly conductive inserts embedded into a rectangular chip exposed to a uniform heat flux

Abstract: Optimization of a highly conductive insert embedded into a heated rectangular chip has been lately investigated. The role of the insert was to gather the heat current within the chip body and remove it to a minimum temperature heat sink. The central goal of this paper is to invoke several reconsiderations, which result in excessive reduction of the peak temperature in the heated chip in comparison with the lowest peak temperature existed in the archival literature. It is proved that for the configuration under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(8 citation statements)
references
References 32 publications
(87 reference statements)
0
8
0
Order By: Relevance
“…They reported a wide range of optimal solutions which allows the user to choose the best design parameters. Hajmohammad et al [30] performed a research related to a highly conductive insert embedded into a chip with uniform heat flux at the bottom surface. They proposed reconsiderations for the system condition to reduce the peak temperature and reported 94% reduction in comparison with the previous study.…”
Section: Introductionmentioning
confidence: 99%
“…They reported a wide range of optimal solutions which allows the user to choose the best design parameters. Hajmohammad et al [30] performed a research related to a highly conductive insert embedded into a chip with uniform heat flux at the bottom surface. They proposed reconsiderations for the system condition to reduce the peak temperature and reported 94% reduction in comparison with the previous study.…”
Section: Introductionmentioning
confidence: 99%
“…These research include, for example, heat transfer in TEG [21,22], thermal analysis of circuit boards [23], airflows in finned heat sinks [24,25], and general hydrodynamics of diffusive processes [26]. Recent advances also include optimal designs and optimization methods, as well as cooling designs with multi-scale techniques [27][28][29][30][31][32][33]. For the investigations of TEG itself, either materials or performance, recent research also include those reported in references [34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…For highly conductive inserts embedded in a rectangular-shaped chip and duct, Hajmohammadi et al also carried out various optimization analyses. 30,31 Towards heat transfer enhancement, recently, highly conductive routes and inverted fins are becoming popular and relevant optimization studies for such systems have been reported in many studies. [32][33][34][35] As compared to the deterministic methods, the convergence of the evolutionary/stochastic methods although relatively slow due to elimination of computing gradients, 36 it is noticed that stochastic/ evolutionary-based optimization algorithms posses several advantages.…”
Section: Introductionmentioning
confidence: 99%
“…also carried out various optimization analyses. 30,31 Towards heat transfer enhancement, recently, highly conductive routes and inverted fins are becoming popular and relevant optimization studies for such systems have been reported in many studies. 3235…”
Section: Introductionmentioning
confidence: 99%